Experimental and theoretical study of internal solitary wave loads on a submerged slender body. (15th March 2023) - Xuan, Pu; Du, Hui; Wang, Shao-Dong; Peng, Pai; Wei, Gang
Abstract: Based on the extended Korteweg de Vries (eKdV) theory and Morison's equation, a theoretical model of internal solitary wave (ISW) loads on a submerged slender body is investigated, and experimental measurements are further carried out in a large stratified fluid flume. The results show that the theoretical results are in good agreement with the experimental results. The horizontal force of the ISW on the slender body is consists of the horizontal dynamic pressure force and the friction force, in which the horizontal dynamic pressure force plays a dominant role. The vertical force includes the vertical wave force and the reduced gravity during the interaction between a slender body and an ISW. The magnitude of the force increases with increasing ISW amplitude, while its direction remains unchanged, and the force is closely related to the submerged depth of the slender body in the density pycnocline, which affects both the magnitude and the direction of the force. Highlights: The ISW force on a submerged slender body is measured experimentally in a stratified fluid flume. A theoretical study of ISW loads is conducted on a submerged slender body based on the Morison equation. The experimental and theoretical results are compared for different ISW amplitudes and submerged depths.